Islam dan Relasi Agama-Agama dalam Perspektif Hadis dan Implementasinya di Lembaga Pendidikan - Sismanto Sismanto (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Islam and the Relation of Religions in the Perspective of Hadith and Its Implementation in Educational InstitutionsAs a pluralistic country consisting of various diverse backgrounds, Indonesia can potentially lead to horizontal conflicts if not managed properly. This article discusses the relationship between Islam and religions, which has become an issue throughout humanity's history. Descriptive research uses the takhrij hadith method and traces information sourced from books and journals that find the topics studied. In editorial terms, some traditions show an accommodative relationship between Islam and other religions, but some seem discriminatory. Thus, there are fluctuations and dynamics of relations between Islam and other religions, with nuances of harmony and disharmony. Therefore, there needs to be a reading of the hadiths constructively implemented in education as a conducive place for teaching Islam multicultural values